Teaching Teachers about Human Rights in Estonia - Haruoja, Merle (Promoting Changes in Times of Transition and Crisis: Reflections on Human Rights Education, 2013)
Modern teacher training in human rights began in 1991, when Estonia regained its independence.Human rights education is included in the civic education curricula. The existing cur-ricula was worked out over several years and from this year we prepared in Estonia in con-currence the teaching materials, human rights trainings and public awareness activities.The Estonian Institute of Human Rights project “Look back into the future – Educa-tion on contemporary human rights issues through an historical lens” aims at enhancing human rights education in Estonia by organising a series of human rights trainings. It brings together history and civic education teachers and non-governmental organisation activists, which will further organise school and out-of-school human rights education activities. The project also aims at setting the basis of a strategic partnership for the ad-vancement of human rights education in the country, as well as a website for networking in the field, as well as functioning as main resource point for Human Rights Education. The project is financed by Foundation “Remembrance, Responsibility and Future” and the project activities are from May 2012 until to February 2013.The lack in Estonia is the comprehensive and systemised Human Rights education together with teachers training and education in Universities.The UN Declaration on Human Rights Education and Training is stimulating in-creased activity in the teachers education area.Teaching human rights in schools starting from teaching the teachers, but unfortu-nately UN Declaration on Human Rights Education and Training is not dealing with the HRE in schools and then the states, NGO-s, teachers’ organisations and students organisa-tions have to take the opportunity to focus on the missing but very important area – teach-ing teachers.